Think Love, Think Peace, Think Harmony: Rethinking on Industrial Tranquility. Issue 1 (January 2021) - Chakraborty, Debarun; Biswas, Wendrila
In this fragmented industrial world, where there are large capital movements, the varied pattern of global trade, fierce challenges and considerable innovations, the holistic approach in workplaces has become a dream! The subtle aspect of the understanding, initiative, cooperation that flows to industrial harmony is essential in organizations to reduce the risk of relapsing into conflicts and strengthens the foundation of its sustainability. The paper probes into the factors that would create and allow industrial harmony and peace to hold and flourish. This would help employees reinforce each other, obtain mental serenity, create a base for realization of their creative potential and stand firm amidst a myriad of challenges and strained situations. Descriptive research with a cross-sectional survey has been conducted on the employees of the selected manufacturing units of West Bengal. Exploratory factor analysis and confirmatory factor analysis has been performed with structural equation modeling on the proposed research model. The prime findings of the study reveal that organizational trust and infusing a tolerant attitude toward conflict in a firm has been instrumental in instilling a sense of harmony and peace in one's mind and spirit. Such an ambience would generate a sense of participation, cooperation and would mutually reinforce social exchange.